Pengembangan Media Pembelajaran Flash Card Digital sebagai Upaya Mengatasi Problematika Keterampilan Berbahasa di Sekolah Dasar: Development of Digital Flash Card Learning Media as an Effort to Address Language Skill Challenges in Elementary Schools - Harpiani, St; Inayah A.M, Muh.; Ampry, Evy Segarawati; Setiawan, Agung; Sridelia, Prita (Institut Agama Islam Daruttaqwa Gresik, 2025)
The issue of language skills in Indonesian language learning in schools, particularly at the elementary level, remains prevalent. In reading skills, many students still struggle with pronouncing words fluently. Regarding writing skills, many students struggle to express their thoughts or ideas in writing due to a lack of inspiration. Furthermore, in listening skills, one prominent problem is that students often lack focus during lessons, resulting in their inability to answer questions posed to them. As for speaking skills, students usually face difficulties in selecting appropriate words, structuring sentences grammatically, and exhibiting confidence. Given the importance of language skills in daily life, effective strategies are needed to address these challenges faced by students. The study employed the ADDIE development model, which encompasses five phases: analysis, design, development, implementation, and evaluation. Data collection was carried out through expert validation sheets to assess media feasibility, as well as teacher and student questionnaires administered during the limited trial phase of the media. Validation by subject matter experts yielded an average score of 94%, classified as “highly feasible,” while validation by media experts resulted in an average score of 95%, also categorized as “highly feasible.” Furthermore, the media received highly positive responses, with average scores of 95% from teachers and 96% from students. These findings suggest that digital flashcards are both well-received and effective, positioning them as a relevant and supportive instructional medium in the context of contemporary digital education.